LOCAL AUTONOMY REGULATION AS A BASIS FOR REGULATIVE POLICY ON LOCAL POVERTY MANAGE - Huda, Khoirul (International Journal of Psychosocial Rehabilitation, 2020)
The existence of the law on regional government is directed to accelerate the realization of community welfare through improved services, empowerment, and community participation, as well as increasing regional competitiveness by paying attention to the principles of democratic equality, justice, and the uniqueness of a region. and society, and improvement. Poverty is one of the causes of the emergence of other social problems. The existence of the regional autonomy law is a government solution in order to give authority to regional governments to make regulative policies in the context of poverty alleviation in the region. Through concurrent government affairs, it becomes the basis for the implementation of regional authority consisting of mandatory and optional governmental affairs. Based on Article 18 paragraph (6) of the 1945 Constitution, the regional government has the authority to make regulative policies in drafting regional regulations on poverty reduction in the regions.